Analysis of Human Resources Readiness in Facing Organisational Digital Transformation Towards Industry 4.0: A Case Study at Instant Cement Manufacturing Company - Muthia Azizah; Yudi Nur Supriadi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Digital transformation poses significant challenges for the Indonesian manufacturing sector in the Industry 4.0 era, demanding human resource (HR) readiness in line with technology adoption. This study analyses HR readiness at PT XYZ, an instant cement manufacturing subsidiary of Major Corporate Group, as it navigates organisational digital transformation. Using a qualitative single-case study design, the population included all PT XYZ employees involved in digital transformation, with a purposive sampling of six key informants: the HR Manager, Production Manager, IT Manager, one Supervisor, and two Production Employees. The instruments consisted of semi-structured interview guidelines, limited observation protocols, and a documentation checklist, analysed through the Miles and Huberman interactive model with thematic techniques for pattern identification. The results indicate an overall positive HR readiness, characterised by a collective understanding of transformation as a change in mindset and culture, supported by inter-divisional collaboration that overcomes psychological resistance and technical obstacles through ongoing training and mentoring. However, generational gaps persist. In conclusion, despite successful adaptation through upskilling, companies need an inclusive strategy for sustainable competitiveness